GAGASAN CALON PERSEORANGAN DALAM PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN DALAM SISTEM KETATANEGARAAN INDONESIA - Aisha, Mitra; Indra, Mexsasai; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The nomination of the President under the Act must be nominated by a political party or coalition of political parties. However, the election of Regional Head, given the opportunity to nominate themselves as individuals. It certainly restrict the people who want to run for President through the individual, as if it were 1945 had arranged that every citizen has equal opportunity in government. Based on this understanding, the authors of this paper formulates two formulation of the problem, namely : first, whether the urgency of independent candidates in the general election of President and Vice President in the state system of Indonesia? second, how the efforts efforts to implement the idea of independent candidates in the general election of President and Vice President in the state system of Indonesia?The research method in this study, first, the type of research is legal normative and descriptive. Second, in this study, the data used by researchers is secondary data. Third, data collection techniques supported by three legal material, namely : primary data, secondary data and data tertiary. After the data collected then analyzed qualitatively, then draw conclusions with deductive thinking method is to analyze the problems of the general form to a special form.From the research, there are two main things that can be inferred. First , the President 's candidacy individuals refers to patterns of local elections . In the Constitutional Court Decision No. 5 / PUU - V / 2007 which discusses judicial Local Government Act, which approved the nomination of the Regional Head through individual selection. However, the opportunity is closed because of the election of President and Vice President must be nominated by a political party or coalition of political parties. This is clearly contrary to Article 28D paragraph ( 3 ) of the 1945 Constitution which says that all citizens have equal opportunities in the government. Second, this time is not considered democratic presidential election since the closure of opportunities for independent candidates, so it is necessary the holding of the fifth amendment to the articles of the 1945 Constitution and was followed by changes in legislation related to election of the President and Vice President.Keywords : Election - President and Vice President - Individual Candidates